STUDY OF BAUXITE DEPOSIT CHARACTERISTICS BASED ON XRD AND XRF ANALYSIS IN PT XYZ, SANGGAU REGENCY, KALIMANTAN BARAT PROVINCE - Zidane Al Bana, Muhammad
This study aims to determine the characteristics of bauxite based on its megascopic appearance, mineral content and elemental geochemistry, and their relationship to the processes that control the genesis and type of bauxite deposit in Bukit 7B. The mineral content and geochemistry of the elements were obtained from the analysis of XRD (X-ray Diffraction) and XRF (X-ray Fluorscene). Sampling and preparations were carried out so that XRD and XRF analysis could be carried out. Samples were prepared by sieving to a size of -500 ?m and reduced in number by the coning and quartering method. The prepared samples were analyzed to obtain a diffractogram, mineral content, and elemental geochemistry in the sample. Besides being analyzed by XRD and XRF, the samples were analyzed for megascopic appearance based on texture, color, and grain size. The results showed that the bauxite deposit at Bukit 7B is kaolinitic bauxite originating from granodiorite rock based on megascopic descriptions of the sample in the form of red to yellow laterite soil and concreted texture. From XRD analysis, it was found that the mineral content of bauxite samples consisted of gibbsite (61.82%), kaolinite (22.53%), quartz (15.55%), and hematite (0.1%) while XRF analysis obtained the main chemical composition with Al2O3 (60.1%), SiO2 (21.2%), and Fe2O3 (16.3%) as well as minor elements with traces of Cr2O3 and ZrO2. The abundance of geochemical elements dominated by SiO2 and Al2O3 indicates the origin of the bauxite deposit is granodiorite which is an intermediate igneous rock with a composition of quartz and plagioclase feldspar. Then the abundance of minerals plotted on the Ternary Composition Diagram will show the studied deposits forming kaolinite bauxite. In addition, the presence of hematite and kaolinite minerals indicates that the mineral dissolution stage in the bauxite formation process has not been effective because the dominant SiO2 indicates feldspar minerals that have not been completely leached.